(untitled) (Proceedings of The International Conference on Economics and Development, 2018)
A green economy requires industrial companies which show a high degree of resource efficiency as well as competitiveness. In times of climate change, energy efficiency represents a major aspect due to its large impact on the reduction of greenhouse gas emissions. Nowadays, energy efficiency means not only consuming less energy, but also using it in times when large amounts of renewable energy is available. From the perspective of the industry, the pursuit of energy efficiency can only be supported if it is integrated as an additional production target. This paper aims at the analysis of legal frameworks and market conditions that encourage the industry to include energy efficiency into their operative management. For this purpose, a model is regarded that realizes a holistic optimization of industrial energy consumption, regional renewable energies and energy storage in a local group of companies. It specifically focuses on the integration of production optimization in a local smart grid context. On this basis, recommendations of actions in economy and politics are derived through the simulation of several what-if-scenarios. The foundation of the analysis builds empirical data from companies in Germany. The central results can be summarized in three observations. First, adequate fluctuating energy prices can be used to motivate the implementation of energy efficiency as target in the production management. Second, a bidirectional demand charge can stabilize a local smart grid. Third, the redistribution of avoided costs for grid expansions can support the installation of energy storages. A future task is the validation of the results in empirical field tests.